2015
DOI: 10.1631/jzus.b1400197
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera extract enhances sexual performance in stressed rats

Abstract: Aphrodisiacs are required to improve male sexual function under stressful conditions. Due to the effects of oxidative stress and dopamine on male sexual function, we hypothesized that Moringa oleifera leaves might improve male sexual dysfunction induced by stress. Therefore, the effects on various factors playing important roles in male sexual behavior, such as antioxidant effects, the suppression of monoamine and phosphodiesterase type 5 (PDE-5) activities, serum testosterone and corticosterone levels, and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 38 publications
6
64
0
Order By: Relevance
“…The sperm concentration found in this study was similar to that reported in the same breed of bulls by Susilawati (2011) andSetchell (2014). The failure of Moringa oleifera to increase the sperm concentration reported in this study was in contrary to that reported in mice by Priyadarshani & Varma (2014) and in rats by Prabsattroo et al (2015). They found that in hyperglycaemic mice and stressed rats, the supplementation of Moringa leaves significantly increased sperm concentration.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The sperm concentration found in this study was similar to that reported in the same breed of bulls by Susilawati (2011) andSetchell (2014). The failure of Moringa oleifera to increase the sperm concentration reported in this study was in contrary to that reported in mice by Priyadarshani & Varma (2014) and in rats by Prabsattroo et al (2015). They found that in hyperglycaemic mice and stressed rats, the supplementation of Moringa leaves significantly increased sperm concentration.…”
Section: Discussionsupporting
confidence: 90%
“…The higher plasma concentrations of testosterone during the Moringa leaves supplementation was in accordance with the study in rats by Prabsattroo et al (2015) and Dafaalla et al (2016). They reported that Moringa leaves supplementation significantly increased serum testosterone in the rat.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The high prevalence of male sexual dysfunction, estimated to affect between 20 to 30% of men, is a source of distress and can lead to reduced quality of life. 8 Animal studies have shown that Moringa oleifera improves sexual performance and drive with postulated mechanisms that partly depend on its antioxidant properties. 8,13,18 The plant is thought to decrease oxidative stress affecting the Leydig cells of the testes, thus allowing more testosterone -which increases libido -to be produced.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other studies have indicated that Moringa oleifera may act as an antibiotic, anti-mutagenic, anti-spasmodic and male sexual enhancer. 2,[7][8] Bryophyllum pinnatum, also known as leaf of life, life plant, and the miracle plant is a perennial herb native to Madagascar 9 but now widely cultivated in tropical areas throughout the world.…”
Section: Introductionmentioning
confidence: 99%